The Effects of Acute High-Intensity Interval Training on Hematological Parameters in Sedentary Subjects - Belviranli, Muaz; Okudan, Nilsel; Kabak, Banu (Medical sciences (Basel), 2017)
The objective of the study was to determine the effects of acute high-intensity interval training (HIIT) on hematological parameters in sedentary men. Ten healthy, non-smoker, and sedentary men aged between 18 and 24 years participated in the study. All subjects performed four Wingate tests with 4 min intervals between the tests. Blood samples were collected at pre-exercise, immediately after, 3 and 6 h after the fourth Wingate test. Hematological parameters were analyzed in these samples. The results showed that hematocrit percentage, hemoglobin values, red cell count, mean cell volume, platelet count, total white cell count, and counts of the white cell subgroups increased immediately after the acute HIIT and their values began to return to resting levels 3 h after exercise, and completely returned to resting levels 6 h after exercise. In conclusion, acute HIIT causes an inflammatory response in blood.